Salvia cualensis and Salvia cualensis var. perezii (Lamiaceae), two new taxa from the Sierra de El Cuale, Jalisco, Mexico - González-Gallegos, Jesús Guadalupe; Castro-Castro, Arturo (Phytotaxa, 2012)
Salvia cualensis and Salvia cualensis var. perezii are described and illustrated from the Sierra de El Cuale, Jalisco, Mexico. These taxa belong to Salvia section Farinaceae. They are similar in their morphology to Salvia jaimehintoniana, which is distributed in northern Sierra Madre Oriental, Mexico. The new taxa can be distinguished from S. jaimehintoniana by their usually shorter petioles, narrow oblong-lanceolate to linear leaf blades, lanceolate and larger floral bracts, longer lower corolla lips, filaments, connectives, and styles. Additionally an expanded description of S. jaimehintoniana is also presented, under which S. jacalana is synonymized.